How does the Dramatic Theology Approach to Purgatory Contribute to the Idea of Merciful Justice in the Case of Sexual Abuse in the Church? - Sentosa, Yosafat Roni (Sekolah Tinggi Teologia dan Filsafat Widya Sasana, 2024)
In cases of serious and complex sexual abuse, the exercise of mercy raises serious controversies and problems regarding the justice that victims of sexual violence deserve. Merciful justice is the idea that under certain conditions it is justified to exercise mercy to the extent that it does more good than harm and does not cause injustice to the victim. Restorative justice, forgiveness, and reconciliation are conditions that allow for the exercise of merciful justice in cases of sexual abuse. Merciful justice is possible in sexual abuse cases when all three conditions are achieved (through long, complicated, and arduous stages and processes). This article offers the idea that the Dramatic Theology approach to purgatory helps to deepen the idea of merciful justice in specific cases of sexual abuse in the Catholic Church. Keywords: Merciful Justice, Dramatic Theology, Purgatory, Restorative Justice, Forgiveness, Reconciliation.